Lumumba : Africa's lost leader - Zeilig, Leo (Life & times (London, England), 2015)
"Patrice Lumumba (1925-61) is perhaps the most famous leader of the African independence movement. After his murder in 1961 he became an icon of anti-imperialist struggle. His picture was brandished on demonstrations in the 1960s across the world along with Che Guevara and Ho Chi Minh. His life and the independence that he sought for the Congo made him a pivotal figure of the 20th century, Lumumba's life marked out some of the key post-war fault lines in the second half of the 20th century; how the Cold War would be fought in Africa and the nature of the independence granted to huge swaths of the globe after 1945. For those fighting in liberation struggles, Lumumba became a figure of resistance to the imperial division of the world"--Publisher's description